Neuromodulation technique helps the development of rehabilitation medicine - WU Jia⁃ling (Chinese Journal of Contemporary Neurology and Neurosurgery, 2022)
Neuromodulation technique not only provides a new idea for the treatment of many diseases, but also has a profound influence on the innovation and development of rehabilitation medicine. Nowadays, the neuromodulation technique in China is in the stage of rapid development, facing great opportunities and challenges, and has broad application prospects. This review intends to describe the mechanism of different types of neuromodulation technologies, and its application status and future development in the field of rehabilitation medicine, in order to promote the application and development of neuromodulation technique in the field of neurorehabilitation in China.